The use of music in Mutual Recovery: a qualitative pilot study - Callahan, Kiley; Schlozman, Steven; Beresin, Eugene; Crawford, Paul (Intellect, 2017)
Mutual Recovery involves caregivers and their clients mutually participating in artistic endeavours to foster resilience in both parties. A qualitative enquiry into the use of group music making (referred to as a ‘Music Jam’) between both the caregivers and clients at a residential treatment facility for adults with developmental disabilities and Schizophrenia was conducted. The purpose of this study was to examine whether shared musical endeavours enjoyed therapeutic and resilience building utility for both the caregivers and clients. A focus group was conducted in which comments were collected and transcribed for qualitative analysis. Themes of enhanced respect and equality among clients for the caregivers, and intrapersonal connectedness and enhanced feelings of community emerged during analysis. Both parties expressed recurrent themes of humility, mutual respect and overall enjoyment. Mutual Recovery practices where caregivers and their clients play music outside of therapeutic settings are an effective means by which resiliency and connectedness can be enhanced in all participants. To this end, other forms of Mutual Recovery deserve greater investigation in order to better examine whether these practices are worth implementing in larger and more varied formats.